Diseño de un modelo de publicidad para comercializar bicicletas importadas de china en una empresa privada, ciudad de Iquitos - Sandoval Lopez, Lohanna Varinna (2024)
The thesis titled: “Design of an advertising model to market bicycles imported from China in a private company, city of Iquitos”, had the purpose of developing an advertising model to market bicycles from the country of China by a private company. The research has a quantitative approach and is applied from a case study with a non-experimental descriptive design. The sample consisted of 30 surveys of current clients and 20 of potential clients; The office work studied the purchase and sale of bicycles from the years 2017 to 2023. According to the data collection instrument, the characteristics of bicycle ownership, use, purchase preference and price were studied. Respondents signed their Informed Consent to give greater confidence in the information, complying with the ethics of all research. According to the proposed hypothesis, the proposed hypothesis is accepted, it is necessary to increase the sale of bicycles and avoid stock because they can deteriorate and mean loss, consequently, advertising is required as given by the sociodemographic aspect and the responses obtained by the users. customers. The advertising model proposal is found as a result of the tesis